Analysis of Land Use/Land Cover Changes 2005–2020 Jagorawi Highway Corridor - Wardani, Tiara Pratiwi Kusumah; Prasetyo, Lilik Budi; Setiawan, Yudi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Infrastructure development has both negative and positive impacts on the surrounding area. Economics growth, improved living standards, education levels, and easy access are the positive impacts of infrastructure development, meanwhile, it also has the consequences on the naturalresource use and environmental impacts from unsustainable consumption and socio-economic consequences for people around the developed areas. With the currently limited land, management needs to be addressed wisely in areas with high demand for land. Infrastructure can be a catalyst for land use change. This study aims to determine land use changes that occurred in 2005, 2010, & 2020 and analyze its driving factors. We used time series data from Landsat imagery taken from Landsat 5 TM (2005 & 2010) and Landsat 8 OLI/TIRS (2020). Visual analysis method was used to identify and classify the eight land use types per each period of Landsat image series. A simple overlay method was applied to determine the effect of the factors of distance from JT Jagorawi, from arterial collector roads, from GT Jagorawi, and from the government center; and population density. The results show that the built-up area increased from 29.72% in 2005, 32.03% in 2010 and 35.82% in 2020. The range distance that has a potential change in land cover is 4 km from JT Jagorawi & GT Jagorawi; 1 km distance from arterial and collector roads; 7.5 km distance from the government center with a population density of < 5,000 to 10,000 people km2.